Self-Assembled Chitosan-g-Poly(itaconic acid) Nanoparticles: A Potential Drug Carrier for Docetaxel - Joy Bell, S. Sheeba; Subhashini, S. (Asian Journal of Chemistry, 2018)
A series of chitosan-g-poly(itaconic acid) nanoparticles (PIACS) were prepared to evaluate their drug delivery application, which was prepared via free radical polymerization using ammonium persulphate as initiator in nitrogen atmosphere. The electrostatic attraction between carboxylic groups of poly(itaconic acid) and amine groups of chitosan lead to the size reduction. All the synthesized nanoparticles were characterized by FT-IR, particle size analyser, zeta potential analyzer, thermogravimetry, scanning electron microscopy and transmission electron microscopy. Drug was loaded to nanoparticle by co-precipitation method. Drug release studies were carried out in 6.8 and 7.4 pH. Drug entrapment efficiency of chitosan-g-poly(itaconic acid) nanoparticles was lying between 93-95 %. Predicted ADMET (PreADMET) was confirmed that plasma protein binding was less. These results highlight the potential of chitosan-g-poly(itaconic acid) nanoparticles as an efficient drug carrier.